Home networking technologies and standards - Zahariadis, Theodore B. (Artech House telecommunications library., 2003)
Annotation "Covering the vast majority of current and emerging home networking technologies, standards, and trends, this practical resource offers a comprehensive understanding of this developing area. Home Networking Technologies and Standards presents an "end-to-end reference architecture," in which the main residential services are identified and their network requirements are fully analyzed. Professionals find detailed coverage of both wireless and wireline technologies, including IEEE 802.11, Firewire, USB, HiperLAN, Bluetooth, IrDA, DECT, X10, and HomePNA, along with higher-layer technologies like OSGi, UPnP, HAVI, and VHN. The book explains how the technologies work, how they have evolved, what their capabilities are, and what markets they target. It also discusses xDSL, cable, fiber, fixed-wireless, and satellite access network alternatives." "Moreover, this forward-looking reference presents the scope, potential applications, operational concept, architecture, and protocol stack of higher-layer technologies that aim to provide convergence between multiple in-home and access networks. The book introduces the concept of the residential gateway (RG) as a single point of network convergence, and explores important considerations for future digital-smart networked homes."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved